INFLUENCE OF BACTERIAL MELANIN ON THE GROWTH AND DEVELOPMENT OF CUCUMBER BOTH IN VITRO AND IN VIVO CONDITIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
At the Institute of Biotechnology RA on the basis of industrial strain Bacillus thuringiensis, which is used in the production of bacterial insecticides, mutant strain was obtained – the producer of water-soluble melanin. The stimulating influence of bacterial melanin preparation was revealed on the growth and development of cucumber both in vitro and in vivo conditions.
Keywords: bacterial insecticides; water-soluble melanin; stimulating influence